Analisis Break Event Point (BEP) Produk Mie Basah Di Kecamatan Kamang Sumbar - Wijayanti, Ruri; Putri, Nazira Aulia; Ariyetti, Ariyetti (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Indonesia has a high level of noodle consumption, including fresh noodles, which are popular for their practicality and distinctive taste. Fresh noodle production presents a promising business opportunity for small-scale entrepreneurs but still faces challenges in managing production costs and setting appropriate selling prices. This study aims to analyze the Break Even Point (BEP) in fresh noodle production to determine the minimum production quantity required to avoid losses. The research was conducted in Kamang Sub-district, Agam Regency, West Sumatra, from September to December 2024 using a survey method through direct observation and structured interviews with a group of women farmers. The results showed that the total fixed costs amounted to Rp 25,353,000 per year, variable costs were Rp 7,175 per pack, and the selling price was Rp 10,000 per pack. The business break-even point is reached at the sale of 8,974 packs or equivalent to Rp 89,586,572 per year. These findings are expected to serve as a practical reference for small business owners in setting production targets, selling prices, and cost management strategies to maintain sustainable operations.